SYNTHESIS AND BIOLOGICAL EVALUATION OF 2-ISONICOTINYL 3, 5-DIARYL -2H-(3-TETRAZOLIUM) CHLORIDE DERIVATIVES - P.VALENTINA; K.ILANGO; G.DEEPA (International Journal of Pharma and Bio Sciences, 2014)
A synthesis of 2-Isonicotinyl 3, 5-diaryl -2H-(3-tetrazolium) chloride (5) was performed starting from isonicotinic hydrazide (1). The treatment of 1 with various substituted aromatic aldehydes afforded the corresponding Schiff’s bases 3. The Schiff’s bases are converted into a series of aryl formazan via diazocoupling which underwent cyclization in the presence of H2O2 and KMnO4 to give substituted tetrazolium derivatives. The titled compounds were characterized physically and analysed structurally by spectroscopic techniques and Elemental analysis. The compounds S1-S12 were screened for antibacterial activity against Escherichia coli(ATCC 14580), Bacillus subtilus(ATCC 700294) and Staphylococcus aureus(ATCC14580), anti fungal activity against Aspergillus niger( NCIM 627) and anti oxidant activity by DPPH method. All the compounds exhibited significant antimicrobial activity and the compound 2-isonicotinoyl-5-(4-methoxyphenyl)-3-(4-sulfamoylphenyl)-2H-(3-tetrazolium) chloride (S3) revealed good inhibitory activity against bacterial and fungal strains. The presences of electron withdrawing substituents in the phenyl ring at 3 and 5 position of tetrazole resulted in more potent compounds for the above evaluated activities.